Phosphate-activated glutaminase expression during tumor development - Aledo, Juan C.; Segura, Juan A.; Medina, Miguel A.; Alonso, Francisco J.; de Castro, Ignacio Núñez; Marquez, Javier (FEBS letters, 1994)
Changes in phosphate-activated glutaminase activities determined in intact cells and isolated mitochondria have been followed during mouse Ehrlich ascites carcinoma development. Glutaminase activities parallel the levels of poly(A) + RNAs encoding for the mitochondrial phosphate activated glutaminase. During the exponential growth phase, maximum activity was observed and the relative abundance of glutaminase mRNA significantly increased with regard to the stationary growth phase. The presented results show that tumor phosphate-activated glutaminase is subject to long-term regulation by differential gene expression.